Maternal and neonatal characteristics that influence early neonatal deaths in a maternity teaching hospital - Dhahir, Asmar A.; Alalaf, Shahla K. (Zanco Journal of Medical Sciences (ZJMS), 2022)
Background and objective: Low early neonatal death reflects health care progress in any country. We aimed to determine the prevalence of early neonatal deaths and the associated maternal and neonatal factors in a hospital-based study. Methods: This audit study was conducted on all newborns in the labor ward and neonatal intensive care unit of a maternity teaching hospital in Erbil city, Kurdistan Region, Iraq, from January 1, 2020, to December 31, 2020. Fetal and maternal factors were determined and correlated with early neonatal deaths. Results: The early neonatal death rate was 6.7%. All categories of preterm deliveries (extreme, very, and moderate preterm) were significantly associated with early neonatal deaths (odds ratios [ORs] = 45.1, 6.2, and 2.1, respectively). The primiparous and grand multiparous women had a higher risk of early neonatal deaths (ORs = 8.4 and 13.0, respectively). Obese women had a higher risk of early neonatal deaths (OR = 3.3). The risk of early neonatal deaths was significantly high when the number of antenatal care visits was less than four (OR = 8.1). Delivery by cesarean section was associated with high risk (OR = 3.8). Regarding the Apgar scores in the first and fifth minutes after birth, early neonatal death was significantly higher among those with severely depressed scores. Conclusion: High parity, inadequate antenatal attendance, obesity, and mode of delivery, were contributing factors to early neonatal deaths. Early prenatal care can assist in the rapid identification and management of risk factors for early neonatal deaths.